New multi-secret sharing scheme based on superincreasing sequence for level-ordered access structure. (24th April 2020) - Basit, Abdul; Chanakya, Patibandla; Venkaiah, V. Ch.; Moiz, Salman Abdul
A new multi-secret sharing scheme (MSSS) that uses a superincreasing sequence and realizes level-ordered access structure (LOAS) is proposed. The novelty of the scheme is that not only a single share for all the secrets is sufficient but also the secrets can be changed without renewing the shares of the participants. The proposed scheme has low communication cost and less overhead for the participant.